The Presidential Appointee's Handbook - DeSeve, G. Edward (Book collections on Project MUSE., 2009)
"Explains the core competencies that distinguish successful presidential appointees. Draws on ideas developed by scholars of public and business management, as well as years of government service. Presents a guide to the key terms, laws, and regulations that new appointees will have to deal with once in office"--Provided by publisher.